Berat Badan Pada Akseptor yang Menggunakan Kontrasepsi Suntik di Puskesmas Singgani Kota Palu - Enggar Enggar; Nurasmi Nurasmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The Family Planning (KB) program is carried out in order to regulate the number of births or space births. Injectable contraception is one of the contraceptive methods that is widely used in Indonesia because it works effectively, is practical to use, is relatively cheap, and is safe. One of the ways injectable contraception works is to cause changes in the menstrual cycle to increase body weight which is the most frequently complained about by injectable contraceptive acceptors. Injection methods are divided into two types, namely 1-month injectable contraceptives and 3-month injectable contraceptives. 1-month contraceptive injection is a type of birth control injection that contains a combination of the hormone Medroxyprogesterone Acetate (progestin hormone) and Estradiol cypionate (estrogen hormone), and 3-month contraceptive injection is an injectable contraceptive containing the Depo Medroxyprogesterone Acetate hormone p (progestin hormone) with a volume of 150 mg. The aim of this study was to analyze differences in body weight among injectable contraceptive acceptors. This type of research uses analytical observational research methods. This research sample was taken using the Accidental Sampling technique with a sample size of 42 respondents. Analysis uses the sign difference test. The sign test results showed that there was a relationship between the use of injectable birth control (P < 0.05) and weight gain.